2009
DOI: 10.1016/j.enzmictec.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of a xylanase from Thermomyces lanuginosus and its functional expression by Pichia pastoris

Abstract: a b s t r a c tA xylanase produced by Thermomyces lanuginosus 195 by solid state fermentation (SSF) was purified 9.3-fold from a crude koji extract, with a 7.6% final yield. The purified xylanase (with an estimated mass of 22 kDa by SDS-PAGE) retained 18% relative activity when treated for 10 min at 100• C and approximately 90% relative activity when incubated at pH values ranging from 6 to 10. Xylanase activity in the purified preparation was significantly enhanced following treatment with manganese and potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…The K m value of the thermostable xylanase from Thermomyces lanuginosus , reported 7.3 mg mL -1 and 60.2 mg mL -1 for soluble and insoluble oat spelt xylan respectively, however, was higher than that of Xyn10A xylanase. Furthermore, the Xyn10A was stable at 85°C for 2h, while Thermomyces lanuginosus xylanase was only stable at 60°C for 1 h [32]. Therefore, it can be concluded that Xyn10A exhibits better enzymatic properties for bioconversion of xylan at even higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The K m value of the thermostable xylanase from Thermomyces lanuginosus , reported 7.3 mg mL -1 and 60.2 mg mL -1 for soluble and insoluble oat spelt xylan respectively, however, was higher than that of Xyn10A xylanase. Furthermore, the Xyn10A was stable at 85°C for 2h, while Thermomyces lanuginosus xylanase was only stable at 60°C for 1 h [32]. Therefore, it can be concluded that Xyn10A exhibits better enzymatic properties for bioconversion of xylan at even higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…13) A single xylanase from T. lanuginosus 195 has been purified 9.3-fold from a crude koji extract, with a specific activity of 6,182 U/mg of protein. 53) Following cultivation by SSF, xylanase from T. lanuginosus 195 exhibited optimal activity at 80 C (data not shown). Furthermore, the crude xylanase preparation was shown be exclusively xylanolytic, with stability demonstrated over a wide pH range (pH 2-10) and at elevated temperatures (30% RA at 100 C).…”
Section: Effect Of Supplemented Carbon Source On Xylanase Productionmentioning
confidence: 99%
“…Furthermore, the crude xylanase preparation was shown be exclusively xylanolytic, with stability demonstrated over a wide pH range (pH 2-10) and at elevated temperatures (30% RA at 100 C). 53) Such characteristics indicate that the xylanase preparation from T. lanuginosus 195 can be used in the treatment of paper pulp, without the need for purification or excessive downstream processing.…”
Section: Effect Of Supplemented Carbon Source On Xylanase Productionmentioning
confidence: 99%
“…), confirming its purity. The specific activity of purified AuXyn11A towards birchwood xylan was 22 714 U mg −1 , which is significantly higher than that of purified Thermomyces lanuginosus 195 xylanase (6182 U mg −1 ) and A. niger xylanase (717.5 U mg −1 ) …”
Section: Resultsmentioning
confidence: 79%